2018
DOI: 10.1063/1674-0068/31/cjcp1803038
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles microkinetic study of methanol synthesis on Cu(221) and ZnCu(221) surfaces

Abstract: First-principle based microkinetic simulations are performed to investigate methanol synthesis from CO and CO 2 on Cu(221) and CuZn(221) surfaces. It is found that regardless of surface structure, the carbon consumption rate follows the order: CO hydrogenation>CO/CO 2 hydrogenation>CO 2 hydrogenation. The superior CO hydrogenation activity mainly arises from the lower barriers of elementary reactions than CO 2 hydrogenation. Compared to Cu(221), the introduction of Zn greatly lowers the activity of methanol sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…It might be mentioned that we have compared our DFT energetics (PBE-D3) with the previously calculated data, as shown in Tables S6 and S7, including the work by Grabow and Mavrikakis (PW91 functional), Wang et al (optPBE-vdW functional), Sun et al. (PBE-D3), and Kattel et al (PW91 functional) .…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…It might be mentioned that we have compared our DFT energetics (PBE-D3) with the previously calculated data, as shown in Tables S6 and S7, including the work by Grabow and Mavrikakis (PW91 functional), Wang et al (optPBE-vdW functional), Sun et al. (PBE-D3), and Kattel et al (PW91 functional) .…”
Section: Resultsmentioning
confidence: 71%
“…It might be mentioned that we have compared our DFT energetics (PBE-D3) with the previously calculated data, as shown in Tables S6 and S7, including the work by Grabow and Mavrikakis (PW91 functional), 64 functional), 65 4 black lines. For CO hydrogenation, the highest energy is 1.67 eV, which takes place at the CHO* + H* step.…”
Section: Reaction Mechanisms On Cu and Cuzn Surfacesmentioning
confidence: 99%
“…In many previous computational studies, the Cu step surface decorated with Zn atoms was assumed as the surface model and became part of the rationalization of the experimental results. ,,,, The introduction of the surface defects (e.g., steps and kinks) in the computational model is based on previous computational and experimental studies which found that they play a critical role in improving the catalytic activity. ,, Meanwhile, the addition of Zn to the Cu steps also gives improvement in the catalytic activity as suggested by calculations; ,, however, the basis of assuming attached Zn at the rigid step edge has not been clearly justified due to the challenge in capturing the true surface property under reaction conditions. In fact, the STM experiments by Sano et al indicated that most of the Zn atoms are eventually substituted homogeneously into the terrace rather than localized at the step edge under vacuum conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Transition metals (TMs) have been widely used to catalyze various chemical reactions in heterogeneous catalysis. , Corresponding catalysts with specific size and shape are prepared to expose more coordinate-unsaturated sites and/or unique ensembles (such as B5 sites) to optimize the catalytic activity and selectivity. Exploring the sensitivity of active sites with different structural motifs is thus important to design new catalysts. Among others, there has been increasing interest in the effect of crystal structures on heterogeneous catalysis and electrocatalysis. The great impact of crystal phases on catalysis mainly comes from their distinct bulk symmetries, which might result in various structural motifs with highly different reactivity and density. Many experiments reported that for Fischer–Tropsch synthesis (FTS) cobalt with a hexagonal closed-pack (hcp) phase is more active than that with a face-centered cubic (fcc) one. Theoretical calculation found that higher activity of hcp Co came from the exposure of more open surfaces with higher intrinsic activity . However, for ruthenium, the fcc phase was able to expose more active sites and therefore have a higher specific activity than hcp Ru, as confirmed by subsequent FTS experiment .…”
Section: Introductionmentioning
confidence: 99%